2017
DOI: 10.1371/journal.pone.0184841
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17-positive mast cells influence outcomes from BCG for patients with CIS: Data from a comprehensive characterisation of the immune microenvironment of urothelial bladder cancer

Abstract: The tumour immune microenvironment is considered to influence cancer behaviour and outcome. Using a panel of markers for innate and adaptive immune cells we set out to characterise and understand the bladder tumour microenvironment of 114 patients from a prospective multicentre cohort of newly-diagnosed bladder cancer patients, followed-up for 4.33±1.71 years. We found IL-17-positive cells were significantly increased in primary and concomitant carcinoma in situ (CIS), p<0.0001, a highly malignant lesion which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
(80 reference statements)
1
30
0
Order By: Relevance
“…As well as detecting a diverse infiltrate of innate and adaptive immune cells including the above mentioned cell types, another study reported a significant role for IL-17 positive mast cells in influencing the outcomes from BCG therapy (20). Patients with carcinoma in situ (CIS, high grade cancer cells that are only in the innermost layer of the bladder lining) with higher numbers of IL-17+ mast cells showed significantly longer event-free survival after intravesical BCG therapy than patients with less IL-17+ mast cells.…”
Section: The Gold Standard Immunomodulatory Approach To Treat Nmibc: mentioning
confidence: 99%
“…As well as detecting a diverse infiltrate of innate and adaptive immune cells including the above mentioned cell types, another study reported a significant role for IL-17 positive mast cells in influencing the outcomes from BCG therapy (20). Patients with carcinoma in situ (CIS, high grade cancer cells that are only in the innermost layer of the bladder lining) with higher numbers of IL-17+ mast cells showed significantly longer event-free survival after intravesical BCG therapy than patients with less IL-17+ mast cells.…”
Section: The Gold Standard Immunomodulatory Approach To Treat Nmibc: mentioning
confidence: 99%
“…Mast cells negative correlated with several types of immune cells, such as macrophages M1/T cells CD8/T cells CD4 memory activated/T cells follicular helper, etc. the result consists with its pro-tumorigenic role in BLCA [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells infiltration has been showed involved in several types of cancer physiological and pathological conditions [30]. Previous studied showed that mast cells influence BLCA patient outcomes [31,32]. Mast cells could enhance bladder cancer metastasis by increasing CCL2/CCR2/EMT/MMP9 signals axis.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have analyzed the immunebiology of CIS. Dowell et al analyzed the effect of Interleukin (IL)-17 positive mast cells on CIS [30]. The investigators observed an increased number of these cells in the CIS environment compared to other types of non-CIS NMIBC.…”
Section: Molecular Biology Of Cismentioning
confidence: 99%